INTERNALISASI NILAI-NILAI KEISLAMAN PADA ANAK-ANAK PARA MUALLAF (Studi Kasus Pondok Pesantren Umar Bin Abdul Azis di Dusun Tolonggeru Kecamatan Madapangga Kabupaten Bima Tahun 2016) - Suryani, Hermawansyah dan (PALAPA: Jurnal Studi Keislaman dan Ilmu Pendidikan, 2017)
This research purpose to describe internalization of Islamic values to muallaf children The Research focus are internalization process, strategy, enabling and inhibiting factors internalization of Islamic values. The main problem is increasing religious conference in tolonggeru village, then more children are mualaf. But with the lack of understanding of Islam background their parents, so that the difficulties for parents provide an understanding of Islam for theirs. Presence The pondok pesantren Umar Bin Abdul Aziz, assist in the internalization of Islamic values to mualaf children. This research uses qualitative descriptive method. The research subject is headmaster of Islamic boarding school, teacher, people and religious figure. data collection techniques using methods of observation, interviews and documentation. data analysis using the phenomenology of interpretive approach, triangulation, and deductive. The results of this research include the first; introduction of tauhid, comprehension syariaâah ahlaq, aqidah,  and realizing value of ilahiah and insaniyah. The second; exemplary strategy, exercise and conditioning, and advisors. Generally, researcher concludes that internalization the values of Islamic by pondok pesantren Umar bin Abdul Azis, to give a positive value for mualaf and positive value for majority people, with socialization style of Islamic values do without claim of the people and always fostering harmony.